STUDY OF TECHNICAL CELLULOSE AS A MATRIX-SORBENT TO DEVELOP EXPRESS ANALYTIC SYSTEM FOR WATER SAFETY CONTROL - Tatiana Maslakovа; Alesya Vurasko; Inna Pervova; Pavel Maslakov; Ludmila Aleshina; Irina Shapovalova (Химия растительного сырья, 2021)
The study presented by the authors is devoted to the study of the properties and the possibility of using technical cellulose from non-wood plant raw materials as a solid-phase matrix to obtain solid-phase reactive indicator systems by the following methods: synthesis method on the base of a hetarylformazane immobilized on a cellulose matrix and development of analytical systems based on preconcentration of the determined metal ion by a matrix with subsequent its «revealing» by the formazan («revealing» method).The article focuses on determination of optimal combinations of chromogenic organic reagents (hetarylformazanes) and cellulose-based matrices for developing solid-phase reaction-based indicator systems. Adsorption features of formazan reagents onto cellulose matrices was studied. It has been established the relation between the reagent molecule structure, composition of cellulose matrix and analytical properties of the test-systems synthesized to determine metal ions. Different approaches were developed and applied to reveal the visually observable and easily measured effect due to cellulose properties as well as properties of hetarylformazanes fixed on the surface of the matrix. This fact allows to control sensitivity and selectivity of solid-phase reactive indicator systems for water quality assessment.